(untitled) (Journal of Human Sciences, 2021)
The health statue triangle in Fezzan region is the reflect to the geographic conditions, and the situational, historical, political, economic and social privacy. thus , the region is characterized with a wide area, it was from the diddle of Tripoli state and south that has a major importance link with Tripoli state centers and north Europe, and the south of Sudan in the nineteenth century in contrast with the European scouting efforts to the insides of African continent. Fezzan was an important pure article by bits healthy history. Through the witness of the most of European voyagers who were already a medical staff. Others hided that they belong to the staff to ease the official mission that s/he was sent for, regarding to the continent which the source article had about foreign /Arabs voyagers diaries about Fezzan , several questions arouses . How were the health conditions in nineteenth century? Did the local/folk medicine and the Fezzan government contribute in curing epidemic treatment and diseases, and what are the reasons? This research paper is divided into four sections, at first , a concise historical geographic background to show Fezzan borders in nineteenth century . secondly , the social, economic , political and geographic efforts on the health statue in Fezzan. Thirdly , the common diseases in Fezzan in the nineteenth century and the ways to cure them, finally, Fezzan power treatment efforts in the nineteenth century.